(untitled) (Periodicals of Engineering and Natural Sciences, 2021)
Electromagnetic vibration energy harvesting is a relatively new technology that transforms kinetic energy from mechanical vibrations into electrical energy, allowing the substitution of batteries or cables for powering ultra-low-power devices like wireless sensor networks for structural health monitoring. For this aim, different magnet and coil configurations have been proposed for the design of these harvesters by several researchers. In this paper, four cylindrical “Magnet in-line coil” configurations with back steel, which include a typical single-magnet, a double-magnet array, and two proposed cylindrical Halbach magnet arrays of three and five magnets, are analyzed using the finite element method and compared in terms of their magnetic flux linkage and transduction factor. The numerical simulations are conducted in all cases with the same materials properties, coil parameters, and geometrical boundaries, the latter consisting of the total cross-sectional area of the magnets and the coil, the air gaps, and the total volume of the transducer mechanism. Furthermore, the design that provides the best performance is analyzed with two different coil configurations. It is finally found that the proposed cylindrical Halbach magnet array with three magnets and one-center coil presents the best results, reaching an average transduction factor of 95.83 Vs/m and a normalized power density of 19.72 mW/cm3g2.